The vegan evolution - Tague, Gregory, author.
1 online resource.
Keywords: "Arguing for a vegan economy, this book explains how we can and should alter our eating habits away from meat and dairy through sociocultural evolution. Using the latest research and ideas about the cultural ecology of food, this book makes the case that through biological and, especially, cultural evolution the human diet can gravitate away from farmed meat and dairy products. The thrust of the writing demonstrates that because humans are a cultural species, and since we are evolving more culturally than biologically, it stands to reason for health and environmental reasons that we develop a vegan economy. The book shows that for many good reasons we don't need a diet of meat and dairy and a call is made to legislative leaders, policy makers, and educators to shift away from animal farming and inform people about the advantages of a vegan culture. The bottom line is that we have to start thinking collectively about smarter ways of growing and processing plant foods, not farming animals as food to generate good consequences for health, the environment, and, therefore, animals. This is an attainable and worthy goal given the mental and physical plasticity of humans through cooperative cultural evolution. This book is essential reading for all interested in veganism, whether for ethical, environmental or health reasons, and those studying the human diet from a range of disciplines, including cultural evolution, food ecology, animal ethics, food and nutrition and evolutionary studies"--